2020
DOI: 10.1101/2020.01.24.918219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic and functional analysis of horizontal gene transfer events in diatoms

Abstract: 1.AbstractDiatoms are a diverse group of mainly photosynthetic algae, responsible for 20% of worldwide oxygen production, which can rapidly respond to favourable conditions and often outcompete other phytoplankton. We investigated the contribution of horizontal gene transfer (HGT) to its ecological success. A systematic phylogeny-based bacterial HGT detection procedure across nine sequenced diatoms showed that 3-5% of their proteome has a horizontal origin and a large influx occurred at the ancestor of diatoms… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 101 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…In contrast to the wide expression of pleiotropic gene families, more than 200 families were identified showing significant enrichment for upregulation in one or a limited number of related conditions (Supplementary Note 5 and Supplementary Figs. [16][17][18][19]. Notably, many of these families were species or diatom-specific and responsive to either sexual reproduction, silica depletion, or bacterial interaction ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to the wide expression of pleiotropic gene families, more than 200 families were identified showing significant enrichment for upregulation in one or a limited number of related conditions (Supplementary Note 5 and Supplementary Figs. [16][17][18][19]. Notably, many of these families were species or diatom-specific and responsive to either sexual reproduction, silica depletion, or bacterial interaction ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…5), 63% share similarity to proteins from other eukaryotes and 60% are functionally annotated. Application of a phylogeny-based horizontal gene transfer detection procedure identified 1741 genes of putative bacterial origin 16 . Assessing the accuracy and quality of S. robusta gene models revealed the successful recovery of 99% of core gene families conserved in Bacillariophyta (Supplementary Note 2, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phylogeny-based HGT study on all sequenced diatoms genomes, 1979 genes were found to be of horizontal origin in diatoms. Furthermore, five vitamin B12 biosynthesis pathway genes were detected as HGT, imparting a competitive advantage to diatoms in cobalt depleted environment, as cobalt is essential co-factor for diatoms [46]. In an iron-scarce environment, diatoms have the ability to reduce their cellular iron requirement and replaces plastid-localized ferredoxin with flavodoxin, using flavin as co-factor.…”
Section: Algal Genomesmentioning
confidence: 99%
“…They are able to provide fundamentally novel information about water ecosystems and their functionality [7]. Since the evolutionary history of diatoms involves multiple endosymbioses and their associated genetic transfers, as well as horizontal gene transfers from bacteria [8,9], it is important to use axenic cultures for genomic [8,[10][11][12] and transcriptomic [13][14][15][16][17] studies.…”
Section: Introductionmentioning
confidence: 99%